Peningkatan Hasil Belajar Bahasa Inggris Siswa Melalui Model Pembelajaran Contextual Teaching Learning (CTL) di SMPN 8 Makassar - Darmawati; Ikhwan Wahidin (Jurnal Pendidikan Terapan, 2023)
This research is a classroom action research that aims to improve English learning outcomes through the Contextual Teaching Learning (CTL) learning model, on the basic competencies of contextually capturing meaning related to social functions, text structure, and linguistic elements of narrative text, oral and written, very short and simple, related to fairytales in the even semester of the 2022/2023 academic year with research subjects as many as 25 students. The technique of collecting observations during the learning process and tests given at the beginning and end of the cycle. Based on the results of data analysis and discussion, the average score for cycle I was 1305 while the classical completeness reached 20 percent. And in cycle II obtained an average score of 1542.5 with classical completeness of 80 percent. The increase in students' English learning outcomes by using the Contextual Teaching Learning (CTL) learning model is characterized by an increasing percentage of categories from the low category in cycle I to the high category in cycle II. Observation data shows an increase in student learning outcomes in learning English during learning. From the results of this study it can be concluded that the Contextual Teaching Learning (CTL) learning model can improve English learning outcomes at SMPN 8 Makassar.